β-blockers in hemodialysis: simple questions, complicated answers - Hundemer, Gregory L (Clin Kidney J, 2020)
In this issue of the Clinical Kidney Journal, Wu et al. present the results of a nationwide population-based study using Taiwanese administrative data to compare safety and efficacy outcomes with initiation of bisoprolol versus carvedilol among patients receiving maintenance hemodialysis for >90 days. The primary outcomes were all-cause mortality and major adverse cardiovascular events over 2 years of follow-up. The study found that bisoprolol was associated with a lower risk for both major adverse cardiovascular events and all-cause mortality compared with carvedilol. While the bulk of the existing evidence favors a cardioprotective and survival benefit with β-blockers as a medication class among dialysis patients, there is wide heterogeneity among specific β-blockers in regard to pharmacologic properties and dialyzability. While acknowledging the constraints of observational data, these findings may serve to inform clinicians about the preferred β-blocker agent for dialysis patients to help mitigate cardiovascular risk and improve long-term survival for this high-risk population.